The quality of price formation at market openings and closings: Evidence from the Nasdaq stock market - Michael S. Pagano; Lin Peng; Robert A. Schwartz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
We assess the quality of opening and closing prices for Nasdaq stocks by examining the effect that opening and closing call auctions (introduced in 2004) have had on price formation. Our use of measurement intervals of one minute or less sharpens the picture of intra-day volatility accentuations: they are concentrated within the first two minutes after the open and the last minute prior to the close, with the overall pattern being stapleshaped rather than U-shaped. We find that Nasdaq's calls have reduced this volatility, reorganized order flow, and lowered volatility persistence. Opening and closing prices had previously contained appreciable transitory components which have been dampened by Nasdaq's market structure innovation
urn:nbn:de:hebis:30-62240
Keywords: G14; D44; 330; Opening Price; Closing Price; Price Discovery; Intra-Day Volatility; Market Microstructure; Equity Markets; Call Market; Nasdaq; Börsenkurs; Volatilität; Wertpapierhandel; Auktionstheorie; Mikrostrukturanalyse; USA